Military Cohorts, Substance Use, and Male-Perpetrated Intimate Partner Violence - Cancio, Roberto (Violence against women, 2021)
This study considers variations of intimate partner violence (IPV) from the point of the perpetrator to test the impact of demographic factors on the type of IPV most prevalent among pre-9/11 and post-9/11 military families from the National Longitudinal Study of Adolescent to Adult Health (1994–2008): Waves I and IV in-home interviews (N = 499). Study findings indicate that the perpetration of physical and sexual IPV depends on the context of veteran cohort and race/ethnicity. Models for substance use and IPV patterns were not similar across military cohorts and/or racial/ethnic groups.